Prognostication of progressive pulmonary fibrosis in connective tissue disease-associated interstitial lung diseases: A cohort study - Chiu, Yu-Hsiang; Koops, Maaike F. M.; Voortman, Mareye; van Es, H. Wouter; Langezaal, Lucianne C. M.; Welsing, Paco M. J.; Jamnitski, Anna; Wind, Anne E.; van Laar, Jacob M.; Grutters, Jan C.; Spierings, Julia (Frontiers in Medicine, 2023)
Background Connective tissue diseases-associated interstitial lung disease (CTD-ILD) is a heterogeneous condition that impairs quality of life and is associated with premature death. Progressive pulmonary fibrosis (PPF) has been identified as an important risk factor for poor prognosis. However, different criteria for PPF are used in clinical studies, which may complicate comparison between trials and translation of study findings into clinical practice. Methods This is a retrospective single center study in patients with CTD-ILD. The prognostic relevance of PPF definitions, including INBUILD, ATS/ERS/JRS/ALAT 2022, and simplified progressive fibrosing (simplified PF) criteria, were examined in this cohort and validated in the other reported Dutch CTD-ILD cohort. Results A total of 230 patients with CTD-ILD were included and the median follow-up period was six (3—9) years. Mortality risk was independently associated with age (adjusted HR 1.07, p < 0.001), smoking history (adjusted HR 1.90, p = 0.045), extent of fibrosis on high-resolution computed tomography (HRCT) at baseline (adjusted HR 1.05, p = 0.018) and baseline DLCO (adjusted HR 0.97, p = 0.013). Patients with regular pulmonary function tests in the first 2 years (adjusted HR 0.42, p = 0.002) had a better survival. The prognostic relevance for survival was similar between the three PPF criteria in the two cohorts. Conclusion Higher age, smoking, increased extent of fibrosis and low baseline DLCO were associated with poor prognosis, while regular pulmonary function evaluation was associated with better survival. The INBUILD, ATS/ERS/JRS/ALAT 2022, and simplified PF criteria revealed similar prognostication.